Factors influencing the community participation approaches used in Aedes mosquito management in the Torres Strait, Australia - Tammy Allen; Alan Crouch; Tanya L. Russell; Stephanie M. Topp (BMC, 2023)
Abstract Background Aedes-borne disease risk is increasing in tropical and sub-tropical regions across the globe. While Aedes-borne disease continues to disproportionally affect low- and middle-income countries, parts of high-income countries, such as the Torres Strait region in Australia are also at risk. The Torres Strait is a group of islands located between Cape York Peninsula in far north Queensland, Australia and Papua New Guinea. The Torres Strait has both Aedes albopictus and Aedes aegypti and is close to Papua New Guinea where dengue fever is endemic. Managing Aedes-borne disease risk requires a range of strategies, including community participation. Existing research shows that high-income countries tend to favour government-led (top-down) informing approaches when engaging communities in Aedes mosquito management. Little is known about the factors that influence the choice of community participation approaches in Aedes mosquito management particularly in a high-income country setting, such as Australia. This research contributes to filling this knowledge gap by exploring the community participation approaches used in Aedes mosquito management and the factors influencing these choices in the Torres Strait. Methods 16 semi-structured interviews were conducted with local government and state government agencies working in Aedes mosquito management in the Torres Strait. Six key mosquito management plans and policies were also reviewed. Thematic analysis was used to identify, analyse and attribute meaning from the data collected. Results A range of community participation approaches were used within the two main Aedes mosquito management programs (Aedes albopictus Elimination Program and the Torres Strait Island Regional Council, Environmental Health Program) in the Torres Strait. These approaches included door-to-door inspections, awareness raising strategies, and community clean-up events. Approaches were chosen for reasons related to regulations, attitude and beliefs, and resourcing. Conclusions This study revealed the use of both top-down and bottom-up approaches to engaging the community in Aedes mosquito management in the Torres Strait. These findings contribute to a better understanding of why bottom-up approaches are used, which is valuable for shaping future policy decisions. This study also provides suggestions on ways to enhance community participation in the Torres Strait, which could also be considered in other similar tropical regions.